Testing of Sinters Made of Copper Powders Coated with Carbon Structure Containing Graphene - Kamil RUTKOWSKI (Badania spieków wykonanych z zastosowaniem proszków miedzi pokrytej strukturą węglową zawierającą grafen, 2021)
This paper presents the results of preliminary tests on specimens made from mixtures of dendritic copper powder (CuE) with the graphene-coated copper powder (CuG) in a range from 20% to 100% (CuG). The properties of the powder mixtures, green compacts and sinters were determined. In order to study the properties of the powder mixtures, the following tests were carried out: a measurement of the CuG powder grain size after the grinding process, measurements of the bulk density and tap density of the prepared powder mixtures. The porosity of the produced green compacts and the sinters was calculated as well as the densification capabilities of the powder mixtures by use die pressing, cold isostatic pressing and sintering in a reducing atmosphere were tested. Moreover, the morphology of the existing pores was analysed using an optical microscope and the Brinell hardness was determined. The measured Brinell hardness of the samples was in the range of 17 HB for sinters made from CuG to 34 HB for sinters made from a 20% CuG powder mixture. More than six hundred measurements that were made in this study show that the high CuG content in the powder mixture reduces the hardness of the sinters as well as increase their porosity.
Keywords: Badania spieków